Emergence of Dengue 4 as Dominant Serotype During 2017 Outbreak in South India and Associated Cytokine Expression Profile - Gowri Sankar, S.; Mowna Sundari, T.; Alwin Prem Anand, A. (Frontiers in Cellular and Infection Microbiology, 2021)
Dengue virus (DENV) infection is prevalent in tropical and subtropical regions of the world, which is fatal if untreated symptomatically. Emergence of new genotype within serotypes led to enhanced severity. The objective of the study is to identify the molecular characteristics of the DENV circulated during 2017 outbreak in Tamil Nadu, India, and to investigate the role of inflammatory cytokines in different “serotypes” and in “dengue severity”. A total of 135 suspected samples were tested for DENV infection using IgM, IgG, and qPCR assay; where 76 samples were positive for DENV and analyzed for 12 inflammatory cytokines using ELISA. Serotyping shows 14 DENV-1, 22 DENV-2, 7 DENV-3, and 33 DENV-4, where DENV-4 was predominant. Among 76, 42 isolates were successfully sequenced for C-prM region and grouped. A lineage shift was observed in DENV-4 genotype. Irrespective of serotypes, IFNγ was significantly elevated in all serotypes than control as well as in primary infection than secondary, indicating its role in immune response. GM-CSF and IP-10 were significantly elevated in secondary infection and could be used as prognostic biomarkers for secondary infection. Our observation shows differential cytokine expression profile varied with each serotype, indicating serotype/genotype-specific viral proteins might play a major role in dengue severity. DENV-4 as dominant serotype was reported in Tamil Nadu for the first time during an outbreak with a mixed Th1/Th17 cytokine expression profile that correlated with disease severity. We conclude it is essential to identify circulating viral genotype and their fitness by mutational analysis to correlate with disease severity and immune status, as this correlation will be helpful in diagnostics and therapeutics applications.